(untitled) (Reflection and Critique Law Magazine, 2020)
It’s true that the changes originating from globalization and technology have caused a series of consequences - positive and negative - in the professional, social, psychological and political environment, accommodating the new technologies to daily practices; It’s also true that such innovation has led to significant changes in the way citizens use virtual social networks for communication, entertainment and entertainment, whether publishing or sharing content on the network. At any rate, the overuse of virtual social networks - such as Facebook, Instagram, Whatsapp, etc. - has produced a number of previously unheard-of situations, including the possibility of a user requiring certain content that is detrimental to their reputation. permanently deleted from the network. However, due to the unhappiness, slowness or inability of the legislature, the rules that exist today and intended for internet users do not guarantee them the possibility of being, in fact, forgotten, or having their names unrelated to certain facts. And it’s from this populated and uncertain environment that this legal institute will briefly address the right to be forgotten in the information society, indicating the need to include this institute in the Brazilian legal system, either due to the inadequacy of the norms, or by the study of the case “Neymar Jr. and Najila Trindade” which will be briefly analyzed.